PENGARUH PENGETAHUAN PERPAJAKAN DAN PENERAPAN E-SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK YANG DI MODERASI OLEH TECHNOLOGY ACCEPTANCE MODEL - Sihar Tambun; Ikhsan Muhtiar (Universitas 17 Agustus 1945 Jakarta, 2019)
This study was conducted to determine the effect of tax knowledge and application of e-system of taxation on the level of compliance of individual taxpayers who moderated by technology acceptance models. This study used two independent variables such as knowledge of taxation and the implementation of e-sytem, and the dependent variable, namely personal tax compliance, as well as moderating variables, namely technology acceptance models.The sample in this study individual taxpayers as much as 82 samples taken randomly via an online questionnaire (https://bit.ly/kuesionerSP). Distributing questionnaires conducted online. The sampling technique in this research is done using probability sampling technique by using simple random sampling technique is sampling of all the population was randomly allotted. The data analysis was done with the help SmartPLS program Partial Least Square.These results indicate that the tax knowledge no effect on tax compliance, while the implementation of e-system and technology acceptance models have a significant positive effect on tax compliance. Technology acceptance models have not been able to moderate the effect of tax knowledge and application of e-system on tax compliance.Keywords: Tax Knowledge, Application of the E-system, Taxpayer Compliance, Technology Acceptance Model.